Streptomyces Strains Induce Resistance to Fusarium oxysporum f. sp. lycopersici Race 3 in Tomato Through Different Molecular Mechanisms - Abbasi, Sakineh; Safaie, Naser; Sadeghi, Akram; Shamsbakhsh, Masoud (Frontiers in Microbiology, 2019)
Abstract Plant growth promoting rhizobacteria (PGPR) are potential natural alternatives to chemical fungicides in greenhouse production via inducing plant immune system against biotic stresses. In this research, 126 Streptomyces isolates were recovered from rhizosphere soils of 13 different commercial vegetable greenhouses in Iran. Streptomyces isolates were screened for in vitro Plant growth promoting (PGP) traits and ability to antagonize Fusarium oxysporum f. sp. lycopersici race 3 (FOL), the causal agent of Fusarium wilt of tomato (FWT). Six isolates with the highest antagonistic activity and at least three PGP traits were selected and compared with chemical fungicide Carbendazim® in a greenhouse experiment. All bacterial treatments mitigated FWT disease symptoms like chlorosis, stunting and wilting at the same level or better than Carbendazim®. Strains IC10 and Y28 increased shoot length and shoot fresh and dry weight compared to not inoculated control plants. Phenotypic characterization and 16S rRNA gene sequencing showed, strains IC10 and Y28 were closely related to S. enissocaesilis and S. rochei respectively. The ability of the superior biocontrol strains to induce antioxidant enzymes activity and systemic resistance (ISR) was investigated.